Innovative PDK1‐Degrading PROTACs Transform Cancer Aerobic Glycolysis and Induce Immunogenic Cell Death in Breast Cancer - Aohua Deng; Renming Fan; Jiakui Gou; Ruoxi Sang; Ruizhuo Lin; Ting Zhao; Junyan Zhuang; Yongrui Hai; Jialin Sun; Gaofei Wei (Exploration)
ABSTRACT Cancer cells are characterized by the Warburg effect, which hijacks glycolysis and hinders OXPHOS. Pyruvate dehydrogenase kinase 1 (PDK1) is a key modulator in the Warburg effect and is highly expressed in tumor cells. We utilize PROTAC technology to design compounds that could achieve long‐lasting degradation on PDK1. After screening anti‐tumor activity in vitro, we selected a top compound A04, among 22 chemical candidates in various structures. Compared to a conventional PDK1 inhibitor, A04 dramatically improves over 1000‐fold proliferation inhibition efficacy. Besides, A04 reverses Warburg effect and causes tumor apoptosis. In vivo, A04 achieves potent therapeutic efficacy in tumor‐bearing mice and dramatically prolongs their lifetime after surgery resection. For the mechanism, A04 induces immunogenic cell death and reverses immunosuppression in the TME to enhance antitumor immunoreactivity. Further, transcriptome analysis verifies the mechanisms and uncovers fluctuation in cancer related pathways. Combination with αPD‐L1 improves therapeutic efficacy and promotes multiple immunocytes infiltration. In conclusion, we first utilize PROTAC technology on modulating aberrant expressed metabolic enzyme PDK1 in cancer cells and achieve a great pharmacological effect, rendering it promising for energy‐aberrant cancer therapy.